ANALISIS STRATEGI PEMASARAN PRODUK BAKERY (STUDI KASUS PADA USAHA NADIA ROTI) ANALYSIS OF MARKETING STRATEGY FOR BAKERY PRODUCTS (CASE STUDY ON NADIA ROTI BUSINESS) - Kamilah Hafsah, Latifah; Nurainy, Fibra; Pratondo Utomo, Tanto; Zulferiynni, Zulferiyenni (Jurnal Agroindustri Berkelanjutan, 2023)
This study aims to analyze internal and external factors that influence the formulation of marketing strategies, formulate alternative strategies and recommend appropriate marketing strategies to be implemented by Nadia Roti's business. The data used in this study were primary data and secondary data. The data obtained were processed and analyzed by IFE (Internal Factor Evaluation) matrix, the EFE (External Factor Evaluation) matrix, the IE (Internal External) matrix, the SWOT matrix (Strengths, Weaknesses, Opportunities, Threats) and QSPM (Quantitative Strategic Planning Matrix). The analysis of the internal and external environment shows that Nadia Roti's business has a solid internal and external environment, so Nadia Roti's company was in quadrant I, namely, grow and build. Four alternative strategies were generated by the SWOT matrix, namely maintaining product quality to compete with its competitors, maintaining good relationships with consumers, implementing digital marketing and conducting product development. The recommended priority marketing strategy was to implement digital marketing.